Development of Android-based Interactive Multimedia Social Impact Informatics (Maksim) in Support of the Independent Curriculum - Nurul Zahratul Faiqah; Nurmayanti Nurmayanti; Agussalim Agussalim (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to examine the viability of incorporating android-based interactive multimedia into the Informatics curriculum for seventh-grade students. The expectation is that the captivating and interactive elements of this multimedia will serve as a catalyst for students to cultivate a deeper understanding of Informatics, regardless of whether they are engaged in a traditional classroom environment or pursuing independent learning from their residences. The ADDIE model, encompassing analysis, planning, development, introduction, and evaluation, was employed as the developmental framework for this study. Based on the results of the study, it was determined that the validation rates for the instrument were as follows: 93% validation by instrument experts, indicating a high level of validity; 81% validation by media experts, also indicating a high level of validity; and 100% validation by content experts, indicating a complete agreement on the validity of the instrument. In addition, it was found that the assessment's accompanying questionnaires were deemed highly applicable by both teachers and students, with a rating of 100% for teachers and 89% for students. The findings of this study indicate that the Maxim multimedia materials developed for the purpose of teaching and learning Informatics in class VII at UPT SMPN 3 Pangsid demonstrate both validity and utility.